Diplomatic Relations and Globalization: A Historical Analysis of China and America during the Post-Cold War Era - Abbas, Syed Tahir (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research delves into the intricate diplomatic ties between China and America, tracing their journey from Cold War adversaries to contemporary partners. The primary objective is to scrutinize the historical evolution of this alliance, emphasizing the blend of political, economic, and strategic factors shaping their complex relationship. The study aims to unravel critical questions surrounding the genesis and progression of the China-America alliance, dissecting diplomatic ties from the Cold War era to the present. Analyzing the influence of the Cold War context on the formation of the China-America alliance. Identifying pivotal milestones in their diplomatic relations during and after the Cold War. Assessing the contemporary nature of the China-America partnership and its implications for regional and global geopolitics. Using a comprehensive historical research design, the study reviews primary sources like diplomatic archives, treaties, and official statements. Secondary sources, including academic works and policy analyses, provide essential context and depth. The research reveals a nuanced interplay of geopolitical, economic, and strategic considerations sustaining the China-America alliance. Critical junctures in their diplomatic history shed light on factors contributing to the partnership's resilience. This research offers a holistic understanding of the historical roots of the China-America alliance, providing insights into contemporary implications. By seamlessly integrating historical analysis with present-day dynamics, the study contributes to broader scholarship on international relations and regional geopolitics.